PERBANDINGAN PEMBIAYAAN PENGADAAN KENDARAAN RODA EMPAT DENGAN SISTEM SEWA GUNA (LEASING) DAN SISTEM BELI PADA PERUSAHAAN DAERAH AIR MINUM KOTA SAMARINDA - Pramudya, Chandra (EKONOMIA, 2012)
Research conducted at PDAM Town Samarinda. Result of conducted research by writer by comparing between bank credit and leasing got by result for the price of Rp.54.836.984,90. From this result can be seen that bank credit more beneficial with advantage percentage for the price of 9,06%. This result show alternative which must be chosen by management.